Association between sociodemographic characteristics and anxiety levels of violence-exposed patients admitted to emergency clinic - hocagil H; Izci F; Hocagil AC; Findikli E; Korkmaz S; Iris Koc M (Neuropsychiatric Disease and Treatment)
Hilal Hocagil,1 Filiz Izci,2 Abdullah Cüneyt Hocagil,1 Ebru Findikli,3 Sevda Korkmaz,4 Merve Iris Koc5 1Department of Emergency, School of Medicine, Bulent Ecevit University, Zonguldak, 2Department of Psychiatry, School of Medicine, Istanbul Bilim University, Istanbul, 3Department of Psychiatry, School of Medicine, Sutcu Imam University, Kahramanmaras, 4Department of Psychiatry, School of Medicine, Firat University, Elazig, 5Department of Psychiatry, Erenkoy Training and Research Hospital for Psychiatric and Neurological Disorders, Istanbul, Turkey Background: Here we aimed to investigate sociodemographic characteristics, psychiatric history, and association between sociodemographic characteristics and anxiety levels of violence-exposed patients admitted to emergency clinic.Methods: This study consists of 73 violence-exposed patients admitted to emergency clinic who were literate and agreed to participate in the study. A sociodemographic data form created by us to investigate alcohol-substance abuse, suicide attempt, previous history of trauma, self and family history of psychiatric disorders and Beck Anxiety Inventory was given to the patients.Results: Of the patients exposed to violence 63% (n=46) were female and 27% (n=27) were male. Of these patients, 68.5% (n=50) were married, 43.8% (n=25) were workers, 34.2% were housewives, 11% were unemployed, and 11% were civil servants. Of the violence-exposed patients, 56.2% (n=41) were primary school, 21.9% (n=16) were high school, and 21.9% (n=16) were university graduates. Smoking and alcohol use rates were 54.8% (n=40) and 17.8% (n=13), respectively. The most common trauma type was assault using physical force with a ratio of 78.1% (n=57). In addition, anxiety scores were high in 42.5% (n=31) and moderate in 9.6% (n=7) of the patients. Mentioned psychiatric disorder was present in 17.8% (n=13) of the patients and 19.2% (n=14) of the patients’ relatives. The correlation between sociodemographic characteristics and anxiety scores revealed that married patients had higher anxiety scores (P<0.01) and patients assaulted by their parents had lower anxiety scores (P<0.00).Conclusion: A total of 63% of the violence-exposed patients admitted to emergency room were females, 56.2% were primary school graduates, and 43.8% were factory workers; this result shows that low socioeconomical status and education level affect exposure to trauma especially in females. In addition, ~20% of the patients and patients’ relatives had a psychiatric disorder and 53.4% of perpetrators were parents, spouses, and children; this result shows that psychiatric history and family relations are one of the issues that should be taken into account and treated. Keywords: violence, emergency, anxiety